PENGARUH LAMAZE EXERCISE TERHADAP SKALA NYERI MENSTRUASI (DYSMENORRHOEA) PADA REMAJA PUTRI DI SMA BUDI MULIA JAKARTA - Veronica Yeni Rahmawati (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Menstrual pain present as cramps (ranging from mild to severe), which may disturb dailyactivities. Lamaze exercise is non pharmacological method which use breathingrelaxation. This research was to analyze Lamaze exercise to reduction of menstrual pain.This study used pra experimental pre post test design. The population was the studentswith menstrual pain at Budi Mulia Senior High School Jakarta. The sampling techniquewas purposive sampling. Thirty one students participated in this study. The independentvariable was Lamaze exercise and the dependent variable was menstrual pain.Instrument which used to measure pain was Visual Analog Numeric Rating Scale. Datawere analyzed with Wilcoxon Signed Rank Test with significance Î± â‰¤ 0.005. The resultshowed that Lamaze exercise decreasd menstrual pain. The result of statistical testshowed significance level p = 0.000 and the deviation between pre and post mean is2.32, which means that there was decreasing menstrual pain in student in pre test andpost test. It can be concluded that Lamaze exercise can influence menstrual pain indecrease respondent of the research. Lamaze exercise can provide a relaxing effect.Further experiment with different respondent characteristic to obtain more wide range ofresult.Keywords: menstrual pain, Lamaze, relaxing effect, non pharmacological method